An acute Q fever with vessel vasculitis: case report - Shijun Guo; Quanle Liu; Jiaqi Yan; Jin Wang; Yingran Zhong; Feng Gao; Yuejia Zhong (Frontiers in Medicine, 2025)
BackgroundQ fever (QF) is a relatively rare zoonotic infectious disease, and complications such as vasculitis and endocarditis are uncommon but severe. This article reports a case of acute QF complicated by vasculitis.Case presentationThe patient presented with a week of recurrent fever. Upon admission, inflammatory markers and liver transaminases were elevated, and a weak positive result for Chlamydia pneumoniae Immunoglobulin M (IgM) antibodies was detected. After treatment with levofloxacin and doxycycline, the fever persisted. Blood metagenomic next-generation sequencing (mNGS) suggested Coxiella species, raising suspicion for acute QF. The antibiotics were switched to moxifloxacin, but fever continued. Autoimmune tests showed positive antinuclear antibodies, and multiple blood cultures were negative. Further positron emission tomography/computed tomography (PET/CT) revealed inflammatory changes at the bifurcation of the right internal and external carotid arteries, as well as the ascending aorta, pulmonary arteries, and descending aorta, suggesting QF complicated by vasculitis. Treatment with methylprednisolone led to gradual resolution of the fever, and rechecked autoimmune antibodies turned negative. The patient did not experience further fever after discharge.ConclusionCurrently, early recognition and diagnostic techniques for QF still require further improvement. As an infectious disease, timely treatment and vaccination for QF remain key areas of focus for future healthcare professionals.